Development Of A New Rain Attenuation Model For The Deployment Of High Altitude Platform Station - Assadeq Abolhaoshat Mansour Albendag
Rain attenuation is the primary source of High Altitude Platform Station's (HAPS) signal degradation, especially for the systems operating at frequencies above 10 GHz. Rain attenuation can have a significant impact on the service availability of radio communication systems that operate in the Ka-band where the rain attenuation is 10 times larger than at C-band. ITU-R rain attenuation model assumes that the entire slant path is completely penetrated by rain, while in reality the signal path does not completely traverse the rain, because the length of the effective path depends on the rain cell size. A model that can predict the earth-space rain attenuation when the signal path is either completely or partially affected by the rain is developed. To implement a complete infrastructure for wireless communications, a satellite can be integrated with HAPS to provide a high capability for the services. Therefore, a new model has been presented to predict the rain attenuation for non-stationary satellites such as the Medium Earth Orbit (MEO) and Low Earth Orbit (LEO). For verification, a new method to predict the rain attenuation for non-stationary sources is proposed. The method uses the convolution theorem to integrate the rain attenuation overall the signal which penetrated into the rain. Based on thirteen years statistical rainfall data with an integration time of one min, an evaluation of predicting the rain attenuation has been conducted for the peninsular Malaysian region to identify the best location for placing the HAPS stratospheric segment. The study was done based on ten ground stations that suffer the highest rainfall intensities on the ground. The best locations for the northern and the southern platform were found to be at Sungai Lembing (4.11° N, 102.88° E), and Tanjung Kling (2.23° N, 102.02° E) respectively, where the best position of the stratospheric segment was investigated using a matrix of 10* 10.